2012
DOI: 10.1038/onc.2011.634
|View full text |Cite
|
Sign up to set email alerts
|

c-Jun N-terminal kinase has a pivotal role in the maintenance of self-renewal and tumorigenicity in glioma stem-like cells

Abstract: Uncovering the mechanisms that govern the maintenance of stem-like cancer cells is critical for developing therapeutic strategies for targeting these cells. Constitutive activation of c-Jun N-terminal kinase (JNK) has been reported in gliomas and correlates with histological grade. Here, we found that JNK signaling is crucial for the maintenance of 'stemness' in glioma cells. Sphere-cultured glioma cells showed more phosphorylation of JNK compared with serum-containing monolayer cultures. Importantly, blockade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
80
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 61 publications
12
80
0
Order By: Relevance
“…On the other hand, accumulating evidence has now come to support the emerging idea that JNK also plays significant roles in the 'promotion' of tumor growth (3)(4)(5). Only recently, an essential role of JNK in the maintenance of the tumor-initiating capacity of glioblastoma stem cells has been documented and added as one of such 'pro-tumor' roles of JNK (6,7). In line with such roles of JNK, aberrant activation of JNK has been increasingly observed in human cancers (3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, accumulating evidence has now come to support the emerging idea that JNK also plays significant roles in the 'promotion' of tumor growth (3)(4)(5). Only recently, an essential role of JNK in the maintenance of the tumor-initiating capacity of glioblastoma stem cells has been documented and added as one of such 'pro-tumor' roles of JNK (6,7). In line with such roles of JNK, aberrant activation of JNK has been increasingly observed in human cancers (3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
“…11 Although JNK1 and JNK2 have been considered redundant kinases, there is evidence for distinct or even opposing functions of JNK1 and JNK2 in tumorigenesis. [12][13][14][15] Thus, it has been reported that JNK2, but not JNK1, is essential for growth of various human cancer cells including lung, 16,17 glioblastoma, 18,19 prostate and skin. [20][21][22] In contrast, a recent study reported that JNK1 is essential for liver carcinogenesis, while JNK2 appears to be dispensable.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the combined actions of JNK1 and JNK2 have been implicated in the proliferation of glioma cells (197). The underlying causes for these different outcomes remain unresolved, but some researchers have proposed a regeneration-based model as the basis of enhanced tumorigenesis, especially in the liver (198).…”
Section: Comparison Of Jnk1 and Jnk2 Functions In Vivomentioning
confidence: 99%